Influence of strong bases on the synthesis of silver nanoparticles (AgNPs) using the ligninolytic fungi Trametes trogii - Kobashigawa, Jesica María (2019)
Silver nanoparticles (AgNPs) were biosynthesized using fungal extract of Trametes trogii, a white rot basidiomycete involved in wood decay worldwide, which produces several ligninolytic enzymes. According to previous studies using fungi, enzymes are involved in nanoparticles synthesis, through the so-called green synthesis process, acting as reducing and capping agents. Understanding which factors could modify nanoparticles’ shape, size and production efficiency is relevant. The results showed that under the protocol used in this work, this strain of Trametes trogii is able to synthesize silver nanoparticles with the addition of silver nitrate (AgNO3) to the fungal extract obtained with an optimal incubation time of 72 h and pH 13, using NaOH to adjust pH. The progress of the reaction was monitored using UV–visible spectroscopy and synthesized AgNPs was characterized by scanning electron microscope (SEM), through in-lens and QBDS detectors, and energy-dispersive X-ray spectroscopy (EDX). Additionally, SPR absorption was modeled using Mie theory and simple nanoparticles and core-shell configurations were studied, to understand the morphology and environment of the nanoparticles. This protocol represents a simple and cheap synthesis in the absence of toxic reagents and under an environmentally friendly condition.